The Contributions of Mgahinga Gorilla National Park Towards Economic Development of Kisoro District: A Case Study of Gisozi Parish. - Munyambabazi, Danny (Kabale University, 2023)
The main of this study was to investigate the contribution of Mgahinga Gorilla National Park towards the economic development of Kisoro District. This study attempted to assess the services offered by Mgahinga Gorilla National Park to the economic development of Kisoro District both quantitative and qualitative techniques were used. The contribution of Mgahinga Gorilla National Park, the problems facing it, and their mitigating measures have been examined and finally, recommendations were given. Wildlife conservation and economic development have remained a statement for tourism and biodiversity conservation to ensure natural capacity equality in Uganda. There was a need to carry out a study to establish why a phenomenon is in place and what should be done to mitigate the problem. It was found out that UW A disburses 20% of park entrance fees called "Revenue Sharing" to improve the socio-economic livelihoods of the people surrounding the area. Other stakeholders include CARE, MBIFCT, USAID, and World Bank Global Environment (WBGE), and others to mention but a few. All these work in collaboration to promote wildlife conservation as well as tourism. The research findings also indicated that people's standards of living improved because of MGNP through providing employment opportunities. It also revealed that local people especially women have had their income improved as a result of the contribution of MGNP since they have a ready market for their crafts like baskets, bags, and hats made from local materials. The researcher's findings revealed that tourists have come with some negative contributions to the local people like cultural degeneration. This is due to some unacceptable habits like Kissing, Hugging, and Indecent dressing among others which have had a big impact on local people, especially tour guides who interact directly with tourists from different areas with different cultures. From the Research findings Recommendations were prescribed for instance if the government of Uganda and Kisoro District local government could make a strong policy governing the contribution of MGNP, and increase the setting up of many campsites, it could help them get more funds from the industry in the form of taxes. The District procedure and marketing Department should sensitize the farmers around MNP on market gardening and other valuable crops to be grown. This is because farmers in surrounding areas still engage themselves in growing traditional crops such as sorghum, wheat, maize, and many others which do not create a market in tourist campsites.